Contractual Economic Loss in New Zealand - "Who, then, is my neighbour" Really? - Kalderimis, Daniel (Victoria University of Wellington Law Review, 1999)
This article is concerned with the issue of when contractual relational economic loss is, and should be, recoverable in New Zealand. Traditionally this question has been narrowly framed as a debate over whether an ancient legal rule should continue to apply. Recent cases, however, have injected this rule with modern analysis. It has become clear that the debate over the rule is really a debate over which concepts should control negligence liability. This article examines both the rule and its modern day implications. The article examines in turn the New Zealand approach, comparative approaches, and the conceptual underpinnings of the debate. The sophisticated Canadian jurisprudence receives particular emphasis. The conclusion is that not only should New Zealand courts reaffirm the old rule, but that doing so now requires a radical rethinking of the basic New Zealand approach to the law of negligence.